Pengenalan Dan Pelatihan Autocad Untuk Meningkatkan Kompetensi Pengetahuan Teknologi Di Masyarakat Desa Paluh Sebaji Kecamatan Pantai Labu Kab. Deli Serdang - Diana Suita; Simon Petrus Simorangkir; Johan Oberlyn Simanjuntak; M. Husni Malik Hasibuan (Jurnal TUNAS, 2022)
The  results of the socialization of the community service team that had been undertaken for 3 days at the Paluh Sebaji village location, Pantai pumpkin sub-district, Deli Serdang district, with village officials, community leaders, youth and the community in general both formally and written data undertaken in the field. Then we get some descriptions of the problem,  i.e .the lack of knowledge about planned development and description. Problem faced by the Paluh Sebaji village government in planned development, especially the Village Office Building Development Planning, herewith as a community service team participant tries to implement the existing knowledge, i.e. helping to describe the construction planning of the Paluh Sibaji village office using the autocad application. and an estimate of the financing issued adjusted for discussions with the village government that will be undertaken  the construction of the Paluh Sibaji Village office.